Effect Of Knowledge On Nutrition Diet Behavior With Attitude To Mediation Functional Foods For Diabetes Mellitus Patients In Surabaya - Christina Esti Susanti; Budianto Tedjasuksmana (Conference In Business, Accounting, And Management (CBAM), 2012)
The aim of this study to determine the relationship between nutrition knowledge on dietary behavior (behavior for people with Diabetes Mellitus diet) with the mediation of attitudes towards functional foods in people with diabetes in Surabaya. Research used the survey method with cross sectional approach. The study population was patients with diabetes in Surabaya. Sampling was done by taking the accidental coincidence of respondents who encountered. Data analysis using SEM analysis.Â Research shows that people with diabetes nutrition knowledge affects attitudes to functional foods and indirectly affect dietary behavior.Key words: nutrition knowledge, attitudes towards functional foods, dietary behaviorÂ